European consensus for the diagnosis of MCI and mild dementia: preparatory phase - Festari, Cristina; Massa, Federico; Ramusino, Matteo Cotta; Gandolfo, Federica; Nicolosi, Valentina; Orini, Stefania; Aarsland, Dag; Frölich, Lutz; Otto, Markus (Alzheimer's & dementia. Diagnosis, assessment & disease monitoring, 2023)
Abstract: Introduction Etiological diagnosis of neurocognitive disorders of middle-old age relies on biomarkers, although evidence for their rational use is incomplete. A European task force is defining a diagnostic workflow where expert experience fills evidence gaps for biomarker validity and prioritization. We report methodology and preliminary results. Methods Using a Delphi consensus method supported by a systematic literature review, 22 delegates from 11 relevant scientific societies defined workflow assumptions. Results We extracted diagnostic accuracy figures from literature on the use of biomarkers in the diagnosis of main forms of neurocognitive disorders. Supported by this evidence, panelists defined clinical setting (specialist outpatient service), application stage (MCI-mild dementia), and detailed pre-assessment screening (clinical-neuropsychological evaluations, brain imaging, and blood tests). Discussion The Delphi consensus on these assumptions set the stage for the development of the first pan-European workflow for biomarkers? use in the etiological diagnosis of middle-old age neurocognitive disorders at MCI-mild dementia stages. Highlights Rational use of biomarkers in neurocognitive disorders lacks consensus in Europe. A consensus of experts will define a workflow for the rational use of biomarkers. The diagnostic workflow will be patient-centered and based on clinical presentation. The workflow will be updated as new evidence accrues.